Revitalisasi Food Court Tapal Kuda Air Salobar Ambon: Pendekatan Tata Ruang, Manajemen Limbah, dan Daya Tarik Wisata Kuliner - Sholeh Hadri; Sri Prasetya Widodo (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The Tapal Kuda Air Salobar Food Court is one of the culinary areas that plays an important role in supporting tourism and social activities in Ambon City. This area offers a variety of local culinary specialties from Maluku which are an attraction for the community and tourists. However, the increase in the number of visitors and the activities of traders have not been fully balanced by the conditions of adequate spatial planning, facilities, and area management systems. This study aims to analyze the existing condition of the Tapal Kuda Air Salobar Food Court from the aspects of spatial planning, waste management, supporting facilities, as well as the potential and challenges of its development as a culinary tourism destination. This study uses a descriptive qualitative approach with data collection methods in the form of field observations and in-depth interviews with key informants, namely area managers, traders, and visitors. The data obtained are analyzed thematically to identify the main problems and potential development of the area. The results of the study indicate that the spatial planning of the Tapal Kuda Air Salobar Food Court has not been able to accommodate the increase in visitor and trader activities due to the lack of clear zoning, limited circulation routes, and spatial planning that develops without integrated planning. Furthermore, waste management in this area is not yet systematic and sustainable, as evidenced by limited trash bins, a lack of waste sorting, and poorly scheduled waste collection. Limited supporting facilities, such as seating and sanitation facilities, also impact the comfort and quality of the visitor experience, especially during peak visitor periods. Nevertheless, the Tapal Kuda Air Salobar Food Court has significant potential as a culinary tourism destination based on local cuisine and a social space, which can be developed through spatial planning, facility improvements, and more integrated area management. This study concludes that the revitalization of the Tapal Kuda Air Salobar Food Court requires a comprehensive approach, emphasizing spatial planning improvements, strengthening waste management, and enhancing the quality of facilities and area management to support the sustainability of culinary tourism and the quality of public spaces in Ambon City.